2022
DOI: 10.1007/s00382-022-06633-2
|View full text |Cite
|
Sign up to set email alerts
|

A convection-permitting and limited-area model hindcast driven by ERA5 data: precipitation performances in Italy

Abstract: This study describes the implementation and performances of a weather hindcast obtained by dynamically downscaling the ERA5 data across the period 1979–2019. The limited-area models used to perform the hindcast are BOLAM (with a grid spacing of 7 km over the Mediterranean domain) and MOLOCH (with a grid spacing of 2.5 km over Italy). BOLAM is used to provide initial and boundary conditions to the inner grid of the MOLOCH model, which is set in a convection-permitting configuration. The performances of such lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 88 publications
2
2
0
Order By: Relevance
“…Furthermore, the results obtained are in line with those of recently produced CP hindcasts over Italy, sharing similar characteristics with SPHERA, and obtained by downscaling ERA5 with the BOLAM/-MOLOCH model (Capecchi et al, 2022) or COSMO model (Raffa et al, 2021;Reder et al, 2022). In Capecchi et al (2022), similar wet frequency biases in reproducing the 90th percentiles of annual, daily and hourly rainfalls are detected for MOLOCH simulations at 2.5 km grid spacing, as opposed to the dry biases detected with the BOLAM run at 7 km. Further, from the analysis of two severe-precipitation events, a higher level of detail in the spatial characterization and less deviation from maximum intensities is maintained with the CP hindcast, despite underestimating the most extreme rainfall observations (by 64% in one case).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, the results obtained are in line with those of recently produced CP hindcasts over Italy, sharing similar characteristics with SPHERA, and obtained by downscaling ERA5 with the BOLAM/-MOLOCH model (Capecchi et al, 2022) or COSMO model (Raffa et al, 2021;Reder et al, 2022). In Capecchi et al (2022), similar wet frequency biases in reproducing the 90th percentiles of annual, daily and hourly rainfalls are detected for MOLOCH simulations at 2.5 km grid spacing, as opposed to the dry biases detected with the BOLAM run at 7 km. Further, from the analysis of two severe-precipitation events, a higher level of detail in the spatial characterization and less deviation from maximum intensities is maintained with the CP hindcast, despite underestimating the most extreme rainfall observations (by 64% in one case).…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies reported multiple benefits related to increased grid resolutions in numerical simulations, allowing an adequate representation of local dynamical features and forcings leading to or intensifying precipitation events (Buzzi et al, 2014;Cassola et al, 2015;Clark et al, 2016;Wahl et al, 2017;Klasa et al, 2018;Cerenzia et al, 2020;Capecchi, 2021). Furthermore, the results obtained are in line with those of recently produced CP hindcasts over Italy, sharing similar characteristics with SPHERA, and obtained by downscaling ERA5 with the BOLAM/-MOLOCH model (Capecchi et al, 2022) or COSMO model (Raffa et al, 2021;Reder et al, 2022). In Capecchi et al (2022), similar wet frequency biases in reproducing the 90th percentiles of annual, daily and hourly rainfalls are detected for MOLOCH simulations at 2.5 km grid spacing, as opposed to the dry biases detected with the BOLAM run at 7 km.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations